Investigating Racism in The Absolutely True Diary of a Part-Time Indian - Shafadila Ariani Alfitria; Ruly Indra Darmawan (Universitas Negeri Semarang, 2026)
Racism remains a persistent global issue that affects individuals and communities through interpersonal discrimination and structural inequality. This study examines the representation of racism in The Absolutely True Diary of a Part-Time Indian by Sherman Alexie, focusing on the experiences of the protagonist, Arnold Spirit Jr. (Junior), as a Native American teenager navigating life between the Spokane Indian Reservation and a predominantly white high school in Reardan. The background of this study lies in the continued marginalization of Native American communities and the need to analyze literary works as reflections of racial realities. The purpose of this research is to identify and analyze the forms of racism depicted in the novel. Using a qualitative descriptive method and applying the racism theory proposed by Benjamin P. Bowser (2017) as the analytical framework, this study examines individual, cultural, and institutional racism portrayed in the narrative. The findings reveal that racism operates simultaneously at personal and structural levels, limiting opportunities while intensifying identity conflict.